The crisis of philosophical reason in Husserl and Zubiri - González Pérez, Ángel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Many proposals for contemporary philosophy change first philosophy into merehistoriography, or an analysis of the language, its dimensions and its historical-social contexts, or a mere journey through the history of a problem and its various developments. The article, naming this situation as being in the labyrinth (the famous Minos's labyrinth) attempts to establish anotherbasis to first philosophy entering into dialogue with two very different proposals still departing from the common approach of Husserl, its creator (the Phenomenology): the search for a foundation in a transcendental subjectivity which already operates from the world of life that Husserl carried out inThe Crisis of the European Sciences and the proposed reality of actuality in the intellective feeling Act by Zubiri with his noologia.
Keywords: first philosophy; geometry; idealization; subjectivity; lebenswelt; entity; act; actuality; feeling intelligence